Strategi Exit dan Keberlanjutan Finansial : Evaluasi Kemandirian UMKM Alumni Jakpreneur Pasca-Intervensi Pemerintah - Junaidi Hendro; Sri Handoko Sakti; Muhammad Natser (Yayasan Putra Adi Dharma, 2026)
The Jakarta Entrepreneur Program (Jakpreneur) was designed as an integrated entrepreneurial ecosystem through Gubernatorial Regulation No. 2 of 2020. The program's primary focus is to transform Jakarta's MSMEs into innovative and independent business units. However, post-mentoring sustainability is crucial. This study evaluates the level of financial independence of MSMEs assisted by Jakpreneur by analyzing the implementation of the 7P framework in various regions. Through a qualitative literature review, it was found that the program's effectiveness is often hampered by